Polyhydroxyalkanoate Production by Caenibius tardaugens from Steroidal Endocrine Disruptors - Juan Ibero; Virginia Rivero-Buceta; José Luis García; Beatriz Galán (Microorganisms, 2022)
The α-proteobacterium Caenibius tardaugens can use estrogens and androgens as the sole carbon source. These compounds are steroidal endocrine disruptors that are found contaminating soil and aquatic ecosystems. Here, we show that C. tardaugens, which has been considered as a valuable biocatalyst for aerobic steroidal hormone decontamination, is also able to produce polyhydroxyalkanoates (PHA), biodegradable and biocompatible polyesters of increasing biotechnological interest as a sustainable alternative to classical oil-derived polymers. Steroid catabolism yields a significant amount of propionyl-CoA that is metabolically directed towards PHA production through condensation into 3-ketovaleryl-CoA, rendering a PHA rich in 3-hydroxyvalerate. To the best of our knowledge, this is the first report where PHAs are produced from steroids as carbon sources.